PENGARUH PEMBELAJARAN “VIRTUAL LEARNING” DAN KEBIASAAN BELAJAR TERHADAP PRESTASI BELAJAR SISWA PADA BIDANG STUDY SEJARAH KEBUDAYAAN ISLAM DI MTs DARUTTAQWA GRESIK - Moh. Syahru Romadhon (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2023)
This study was conducted to examine Virtual Learning learning applications and habits in improving student achievement in the field of Islamic Cultural History at MTs Daruttaqwa Gresik, with the aim of knowing how the application of Virtual Learning learning at MTs Daruttaqwa Gresik, how students' study habits and learning achievements in the field of Islamic Cultural History at MTs Daruttaqwa Gresik, and whether there is an influence of Virtual Learning learning in improving student achievement in the field of Islamic Cultural History at MTs Daruttaqwa Gresik. This type of research uses quantitative research. And the data collection is carried out by questionnaire, observation, interview and documentation methods. Then the data is analyzed using statistical formulas. The results of this study, showed that the e-learning method had no significant effect on the learning achievement of SKI subjects. Because the significance value is 0.278 and the value is greater than the probability of 0.05 (0.278 > 0.05). From the results of this study, study habits have a significant influence on the learning achievement of SKI subjects. Because the significance value is 0.000 and the value is smaller than the probability of 0.05 (0.000 > 0.05). From the results of this study, e-learning methods and study habits do not affect each other's learning achievement in SKI subjects. Because the significance value is 0.533 and the value is greater than the probability of 0.05 (0.533 > 0.05). So this test shows that Ha was rejected and Ho was accepted, so there is no significant influence of e-learning methods and study habits on learning achievement in SKI subjects at MTs Daruttaqwa Gresik Regency.